Perceptions of food naturalness and the influence of ingredient statements, colors, and flavors - Murley, Tyler (Kansas State University, 2019)
Food selection and consumer behavior are popular topics of study due to the benefits to both academics and food producers. A less studied area, however, is consumer perceptions of naturalness. Neither the U.S. Food and Drug Administration nor the U.S. Department of Agriculture have an official definition for what constitutes as a natural food, although both organizations have general guidelines. This, combined with a lack of consumer understanding of the term, make natural food a complex and important topic to study. Work has been done to study the consumer definition of natural and perceptions of natural food, but no work has studied how food ingredient statements affect consumer perceptions of product naturalness. The objectives of this study were (1) to understand how food ingredient statements influences perceptions of naturalness, (2) to understand how ingredient statement length impacts perceptions of naturalness, (3) to understand how artificial and natural colors and flavors influence perceptions of naturalness, and (4) to understand how product identity and ingredient statements affect naturalness perceptions of whole, non-processed foods. An online survey was launched in the United States, United Kingdom, and Australia, recruiting 1000 consumers in each country. The results of the survey found that consumers use several cues to determine the naturalness of a food product. Product identity has a large impact, but naturalness perceptions can be influenced by the presence of an ingredient statement. Both artificial colors and artificial flavors are perceived as less natural by consumers, but other ingredients also have an effect. Products with ingredient statements that contain a high volume of ingredients with unfamiliar, chemical sounding names lower perceptions of naturalness. Additionally, products with longer ingredient statements are perceived to be less natural than products with short ingredient statements. The location of certain ingredients within the statement also influence naturalness perceptions. When the colorant was located at the end of the ingredient statement, the product was perceived as less natural than when the colorant was located in the middle. Products that come from plants and products that are physically processed are seen as more natural than products with unhealthy ingredients and products that are highly processed. In general, males, Millennials, and consumers with more education and higher income perceived the presented food products as more natural than others in their respective demographic groups. There were also no large differences in perception between US, UK, and Australian respondents. The results from this research project help to form a more complete picture of consumers’ perceptions of natural food and help to understand the importance of ingredient statements in forming these perceptions.
Keywords: Artificial; Colors & Flavors; Food; Ingredient Statement; Natural; Perception